Debt Management Performance Assessment : Guinea-Bissau - World Bank (Washington, DC, 2013)
The objective of the mission was to evaluate current government debt management practices in Guinea-Bissau using the Debt Management Performance Assessment (DeMPA) tool. The assessment will establish a benchmark for monitoring progress over time and provide an analytical background for reform programs developed by the authorities in partnership with their technical and financial partners, and providers of technical assistance in the area of debt management. This report presents the findings of the mission based on information available as at 4 September 2009. Section two explains the DeMPA methodology. Section three provides the country context for the evaluation. Section four presents the mission's detailed assessment of current debt management practices. Section five concludes and discusses potential next steps. This report has been peer-reviewed by debt management experts and World Bank staff, and is being submitted to the authorities of Guinea-Bissau for their review and comment prior to finalization. The final mission report will be transmitted to the authorities for use and disclosure at their sole discretion.